Pelanggaran Prinsip Kesantunan Berbahasa Perempuan Jawa oleh Tokoh Bu Tejo dalam Film “Tilik The Series” (Kajian Sosiopragmatik) - Alfi, Kunti Zahrotun (UIN Raden Mas Said Surakarta, Indonesia, 2023)
This study discusses the violation of the politeness principle in Javanese women by the character Bu Tejo in the film